Contract Design for "Enterprise+Farmer" Sharecropping Family Farms — A Comparison of Institutional Evolution in American and French Family Farms - Guo, Yixuan; Yu, Ping; Liu, Xiao; Xu, Guanqiao (Asia Pacific Economic and Management Review, 2026)
In the process of agricultural modernization in the United States and France, land concentration and farm mergers have been carried out. However, due to the differences in the initial conditions of land resource endowment and the dependence on the path of institutional development, the two countries have formed different institutional evolution results. China’s agricultural development urgently needs to take the road of scale. Based on the existing agricultural basic conditions, small and medium-sized family farms have become a realistic choice. However, compared with professional farmers in developed countries, small farmers in China have congenital shortcomings, and it is difficult to spontaneously grow into the main body of modern large-scale agricultural business. The "enterprise + farmers" proposed in this article is divided into a cooperation model. Enterprises provide all-round support to small farmers with their capital, technical and management advantages, providing an important growth path for small farmers to grow into family farms, which will become the main organizational form of China’s agricultural modernization suitable for national conditions.